Endocrine gland growth as the developmental switch for insect diapause - Kou Wang; Zhong Tian; Kirst King-Jones; Fen Zhu; Xiao-Ping Wang; Wen Liu (Proceedings of the National Academy of Sciences, 2026)
Many animals rely on diapause to survive unfavorable seasons, but how environmental cues are transduced into endocrine changes remains poorly understood. In insects, reproductive diapause is triggered when juvenile hormone (JH) production from the corpora allata (CA) is suppressed, yet the regulatory basis of this suppression is unclear. Here, we show in the cabbage beetle ( Colaphellus bowringi ) that seasonal photoperiod controls CA growth, which in turn sets the gland’s capacity for JH biosynthesis and reproductive fate. Under long-day (LD), diapause-inducing conditions, the CA and its nuclei are smaller than those under short-day (SD), reproductive conditions. To uncover the mechanism, we generated photoperiod-resolved CA transcriptomes and compared them with whole-body profiles, identifying hundreds of CA-enriched and photoperiod-responsive transcripts, including many associated with DNA replication. From these datasets, we selected 54 candidate transcriptional regulators for RNAi screening. This screen uncovered two key factors, retained ( retn ) and ventral veins lacking ( vvl ), which act in the CA to promote DNA replication, gland growth, and JH production. Mechanistically, retn functions upstream of vvl , and together, they activate extra macrochaetae ( emc ), which encodes a downstream transcription factor that further promotes CA growth. Silencing retn , vvl , or emc reduced CA and nuclear size, lowered hemolymph JH titers, and induced diapause-like ovarian arrest and lipid accumulation. Application of the JH analog methoprene reversed these effects. Our findings provide genetic evidence that endocrine organ growth itself is a causal switch for seasonal diapause, revealing how photoperiod-responsive transcriptional cascades can shape endocrine plasticity to mediate seasonal adaptation.